2019
DOI: 10.35944/jofrp.2019.8.1.007
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal accounting accrual Management by internal and external Market Discipline: The case of Tunisian banks in the context of the ‘Arab Spring’

Abstract: Problem/Relevance: This paper deals with such market disciplinary factors as shareholder ownership, audit committee composition and Basel III prudential regulation affecting accounting manipulation measured by abnormal accruals in Tunisian banks in the event of managerial deviation from regulatory requirements Research Objective/Questions : The aim of this study is to estimate the abnormal accruals that measure the accounting manipulation, and to test the effect of disciplinary and regulatory factors according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In this context, Gassouma (2019) found that, after the Arab revolution, which occurred in Tunisia in 2011, abnormal accounting accruals and manipulation increased significantly. This increase in corruption mainly occurred due to the absence of market discipline, the inefficiency of external audits, and the conflict interest between shareholders and managers.…”
Section: Uncertainty Corruption and Economic Growthmentioning
confidence: 96%
“…In this context, Gassouma (2019) found that, after the Arab revolution, which occurred in Tunisia in 2011, abnormal accounting accruals and manipulation increased significantly. This increase in corruption mainly occurred due to the absence of market discipline, the inefficiency of external audits, and the conflict interest between shareholders and managers.…”
Section: Uncertainty Corruption and Economic Growthmentioning
confidence: 96%
“…As a consequence, these companies turn to earnings management to relieve these negative effects. In this context, Gassouma (2019) highlighted that earnings management grew significantly after the revolutions of the Arab Spring in the 2010s, as auditors and regulators lost some of their monitoring power over the accounting practices. Thus, these unusual economic conditions of Jordan motivate this study to provide a different insight into earnings management practices in the country.…”
Section: Rationale Of the Studymentioning
confidence: 99%